INTERNALISASI NILAI-NILAI KOMUNIKASI PROFETIK DALAM MENGEMBANGKAN LINGKUNGAN BERBAHASA ARAB - Syagif, Ahmad (Fitrah, 2024)
The aim of this research is to identify relevant prophetic values and the model for developing an Arabic-speaking environment based on prophetic communication. The type of research used is a literature study and descriptive-analytic technique to describe the research problems based on literature data taken from writings, papers, journals, and relevant scientific articles or books. Furthermore, it examines how the internalization of prophetic communication values can develop an Arabic-speaking environment. The findings indicate that the prophetic communication values relevant for implementation in education and learning should be based on the four prophetic traits with the vision of humanization, liberation, and transcendence in the forms of qaulan (words) sadidan, balighan, kariman, ma’rufan, layyinan, and maysura. This can be internalized in the Arabic-speaking environment development program by creating a positive learning atmosphere, building strong relationships, developing language skills holistically, creating an environment that supports language practice, and setting an example in language use.